Pickup on South Street [videorecording (DVD)] - Fuller, Samuel, 1912-1997; Fuller, Samuel, 1912-1997; Widmark, Richard; Peters, Jean, 1926-2000; Ritter, Thelma; Vye, Murvyn, 1913-1976; Stone, Milburn (Criterion collection, 2004)
Petty crook Skip McCoy has his eye set on the big score. When the three-time convict picks the pocketbook of unsuspecting Candy, he finds a haul bigger than he ever could have imagined: a strip of microfilm bearing confidential U.S. secrets. Tailed by the Feds and the unwitting courier's Communist puppeteers, Skip and Candy find themselves in a precarious gambit that pits greed against redemption.